No Sharing! Ein Mixed-Methods-Ansatz zur Analyse von Kurzzeitvermietungen und ihren sozialräumlichen Auswirkungen am Beispiel der Stadt Salzburg - Smigiel, Christian; Hof, Angela; Kautzschmann, Karolin; Seidl, Roman (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
Short-term rentals in general and Airbnb in particular are currently in the public focus. Using the example of the city of Salzburg with a mixed-method approach, this paper examines both the spatial characteristics and the stake-holder structure associated with this form of platform urbanism. Specifically, the paper provides insights into the spatial distribution, supply and revenue structure, motives of hosts and effects of Airbnb on the housing market. It becomes evident that Airbnb’s idea of shared housing in the sense of the so-called home sharing plays a subordinate role. A new market has developed between the hotel business and regular apartment rentals, which is determined primarily by commercial providers serving the Airbnb market in Salzburg. We argue that Airbnb creates a new form of rent gap, which is no longer preceded by a prior devaluation of districts. This earnings gap now also arises in urban areas that can be described as stable in terms of both price and socio-demographics, since profit increases can be achieved within a very short period of time and with little financial effort. The effects on the housing market are significant, especially in the heavily touristic frequented inner city areas of Salzburg, which cause or intensify processes of change.
Keywords: Short-term rentals; Airbnb; Mixed-method approach; Hosts; Rent gap; Housing market; Salzburg